Ownership: Evolution and Regulation - Franks, J; Mayer, C; Rossi, S (2008)
This article is the first study of long-run evolution of investor protection and corporate ownership in the United Kingdom over the twentieth century. Formal investor protection emerged only in the second half of the century. We assess the influence of investor protection on ownership by comparing cross-sections of firms at different times in the century and the evolution of firms incorporating at different stages of the century. Investor protection had little impact on dispersion of ownership: even in the absence of investor protection, rates of dispersion of ownership were high, associated primarily with mergers. Preliminary evidence suggests that ownership dispersion in the United Kingdom relied more on informal relations of trust than on formal investor protection.